Longitudinal Analysis of Reticular Drusen Associated With Geographic Atrophy in Age-Related Macular Degeneration - Steinberg, Julia S.; Auge, Jasmin; Jaffe, Glenn J.; Fleckenstein, Monika; Holz, Frank G.; Schmitz-Valckenberg, Steffen (Investigative ophthalmology & visual science, 2013)
To characterize longitudinal changes of reticular drusen (RDR) in subjects with geographic atrophy (GA) secondary to age-related macular degeneration in the multicenter, prospective natural history Geographic Atrophy Progression Study. Three-field confocal scanning laser ophthalmoscopy fundus autofluorescence (cSLO FAF, excitation [exc.] = 488 nm; emission [em.] 500-800 nm, Heidelberg Retina Angiograph/Spectralis) of 44 eyes of 22 patients with RDR (median age 77.6 years; range, 61-90 years) at baseline were identified in the study population and included for further analysis. Two independent readers determined the presence, topographic distribution, and pattern of RDR at baseline and at 18 months. Furthermore, the convex hull of the extent of RDR as the minimum polygon encompassing the entire area of RDR involvement was quantified. RDR lesion boundaries were clearly detectable in all directions within three-field FAF composite images in 16 eyes of 10 patients at both baseline and final visits. Over time, RDR-affected retinal area and RDR density increased. Quantitative analysis showed a mean average RDR extent of 53.7 mm(2) (95% confidence interval [95% CI]; 40.7; 66.8) at baseline. The mean differences for intraobserver agreements were 2.4 mm(2) (95% CI; -0.1; 4.9) for reader 1 and -0.6 mm(2) (95% CI; -2.3; 1.1) for reader 2. The mean difference of interobserver agreement was 0.9 mm(2) (95% CI; -0.8; 2.7). A mean growth rate of the RDR extent within the three-field FAF composite image of 4.4 mm(2)/y (95% CI; 1.9; 6.9) was measured. In vivo cSLO FAF imaging allows for both qualitative and quantitative mapping of longitudinal changes of RDR areas within a relatively short time period. Continuous enlargement of the affected retinal area indicates disease progression with regard to this phenotypic characteristic associated with GA in AMD. Systematic recordings of RDR progression appears warranted in future natural history and interventional studies in dry AMD. (ClinicalTrials.gov number, NCT00599846.).